Mass Balance Calculations of Illicit Drugs in Stoke Bardolph Sewage Treatment Works, United Kingdom - Mustapha, Olajide A.; Coffey, Michael; Birkett, Jason W. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
Work encompassed in this study directly measures illicit drug removal rates in laboratory studies. Researchersemployed removal rate data in calculating mass balances in sewage works which is an improvement over priorstudies where assumptions on removal rates at Sewage Treatment Works were made. The batch tests dataenabled determination of degradation of the compounds at different temperatures and times, using varioussludge types after characterization. Mass balances for the Stoke Bardolph Sewage Treatment Works wereconstructed using the removal rate data from the batch studies. Final effluent concentrations of 10.0 ng L-1(morphine), and 80.0 ng L-1 (6-monoacetylmorphine), were recorded after a total of 8 hour hydraulic times (8HRT) from an initial influent concentration of 50 mg L-1. A projected influent concentration of morphine (1.4 gL-1) at Stoke Bardolph was derived from back-calculating measured final effluent concentrations using thesame mass balance approach